EFEK PENGGUNAAN DOUBLE DAN SINGLE PISTON CALIPER TERHADAP WAKTU DAN JARAK TEMPUH PADA PENGEREMAN SEPEDA MOTOR 125 CC - Sopiyan; Darwin Rio Budi Syaka; Muhammad Rafif Iqbal (Jurnal Konversi Energi dan Manufaktur, 2023)
This study aims to determine the distance and braking time on 125cc motorcycle vehicles by using two types of callipers, namely single-piston and double-piston callipers. The research method uses experimental methods. There this method will compare 2 variables to get the results of the study by sulking on SNI Braking. By varying the two callipers of different types and using the brake pressure gauge, stopwatch, and meter to find out the pressure, time, and distance when conducting the test, the results of the test are calculated by the formula of regularly changing straight motion force (GLBB) slowed down, braking force and braking efficiency formula in order to get more valid results. Based on the results of this research report, it was concluded that the 2-piston callipers are superior to the 1-piston callipers in terms of average mileage of 0.51 m (9.81 m – 9.30 m) in front wheel braking and average mileage of 0.42 m (4.63 m – 4.21 m) in rear wheel braking and average stopping time of 0.21 s (2.51 s – 2.30 s) with the average effect of braking efficiency value of 5% (57% - 52 %) on front wheel braking and the average time for 0.21 s (1.58 s – 1.37 s) with the average effect of efficiency value of 5 % (47 % - 42 %) on rear wheel braking. So that makes 2-piston callipers better used in 125 cc vehicles than 1-piston callipers in terms of braking aspects.